Decipher the inhibitory potential of phytocompounds from Leptadenia reticulata on dopamine D2 receptor to enhance prolactin secretion - Sharma, Roshan Kumar; Jalalpure, Sunil S; Chouhan, Mahendra Kumar; Deshpande, Sanjay; Acharya, Rabinarayan; Hegde, Satisha (Drug Research, 2022)
Dopamine is secreted by the hypothalamus, which inhibits the proliferation and effectiveness of lactotroph cells that release prolactin via dopamine D2 receptor (D2R). D2R activation inhibits lactotroph cell prolactin synthesis and regulates prolactin gene expression. Although, commercial medications are available for hypogalactia and agalactia, various plant sources significantly alleviate these problems. Leptadenia reticulata (Jivanti) is one of the important medicinal plants often consumed by nursing mothers to improve breast milk production. However, mechanism and chemical constituents involved in the inhibition of D2R by Jivanti is unclear. Therefore, in this study the phytocompounds reported from Jivanti were used for in-silico analysis to predict D2R inhibitory potential. The binding affinity value of campesterol and β-sitosterol (− 10.1 and −10.0 kcal/mol) with D2R has high revealed by molecular docking and stable interaction reveled by molecular dynamics simulation. Thus, these lead compounds could exert more D2R inhibitory activity resulting into prolactin release, which may lead to an increase in breast milk production. Although all selected compounds had fine permeation, non-toxic, and non-carcinogenic characteristics predicted by ADMET, campesterol had good solubility, absorption characteristics compared to other. Therefore, Jivanti, which is traditionally known medicinal plant, could be explored as a medication candidate to boost breast milk production.
Keywords: Jivanti; Dopamine D2 Receptor; Molecular docking; Prolactin